Pengukuran Risiko Value At Risk (Var) Pada Investasi Saham Menggunakan Metode Simulasi Monte Carlo Studi Kasus: PT. Ultrajaya milk indusrty Tbk - Fajar Maulana; Fitri Sri Mulyani; Ahmad Fitri (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study aims to measure the investment risk of PT Ultrajaya Milk Industry Tbk's stock using the Value at Risk (VaR) method with the Monte Carlo Simulation approach. This quantitative study was conducted at the Actuarial Science Study Program, Universitas Cipasung, Tasikmalaya. The population comprises all stock price data of PT Ultrajaya Milk Industry Tbk listed on the Indonesia Stock Exchange (www.idx.co.id) and Yahoo Finance, with the sample determined through purposive sampling consisting of quarterly stock return data for the 2019–2024 period (24 observations). The research was conducted by analyzing stock return data and testing data normality using the Kolmogorov-Smirnov and Shapiro-Wilk tests. The results indicate that the stock return data are normally distributed, with significance values of 0.200 for the Kolmogorov-Smirnov test and 0.701 for the Shapiro-Wilk test, both exceeding the 0.05 significance level. The VaR calculation at the 95% and 99% confidence levels produced a value of 1,153.482. This value represents the maximum potential loss that investors may experience within the specified investment period. The findings show that the Monte Carlo Simulation method is effective in measuring stock investment risk because it provides a more comprehensive risk assessment by simulating various possible market conditions. The results of this study are expected to serve as a useful reference for investors in making investment decisions and managing stock investment risks.